Trito-Isaiah and the Reforms of Ezra/Nehemiah Consent or Conflict? - Berges, Ulrich 1958- (2017)
The relationship between Trito-Isaiah and the Books of Ezra/Nehemiah is a highly disputed issue. Does the last main part of the Book of Isaiah support the reforms of the two Persian officials or does it constitute a prophetic counter-program? The article steers a middle course by re-evaluating the correct observations of both positions. The focus on Jerusalem constitutes an important link. Nevertheless, in Trito-Isaiah the massive ethnic orientation of Ezra/Nehemiah is supplemented if not rescinded by the concentration on ethical issues. The decisive break line is not the openness towards proselytes but the radical expansion of YHWH’s worship.